Access to Silylated Pyrazole Derivatives by Palladium‐Catalyzed C−H Activation of a TMS group. Issue 28 (7th June 2016) - Mistico, Laetitia; Querolle, Olivier; Meerpoel, Lieven; Angibaud, Patrick; Durandetti, Muriel; Maddaluno, Jacques
Abstract: A simple and efficient approach to new silylated heterocycles of potential interest in medicinal chemistry is presented. A set of bromophenyl trimethylsilyl pyrazole intermediates can be transformed by direct organometallic routes into two families of regioisomeric iodoaryl substrates; using either arylzinc or aryllithium chemistry, the TMS group remains on the pyrazole ring or translocates to the aryl moiety. These two families can then be efficiently transformed into benzo silino pyrazoles thanks to a single‐step cyclization relying on the Pd‐catalyzed activation of a non‐activated C(sp 3 )−H bond alpha to a silicon atom. The experimental conditions used, which are fully compatible with the pyrazole ring, suggest that this reaction evolves through a concerted metalation–deprotonation (CMD) mechanism. Abstract : New silylated heterocycles of potential interest in medicinal chemistry can be easily prepared from bromophenyl trimethylsilyl pyrazole intermediates. These are transformed, by two direct organometallic routes, into regioisomeric iodoaryl substrates that undergo a Pd‐catalyzed C−H activation of a methyl of the TMS group. This reaction closes nicely the central heterocyclic core of the target structure.